The spectrum of giant cell arteritis and polymyalgia rheumatica: a longitudinal prospective study to assess for subclinical giant cell arteritis in new onset polymyalgia rheumatica - Yasser El Miedany; Maha El Gaafary; Mathias Toth; Sami Bahlas; Waleed Hassan; Safaa Mahran; Mohammed Hassan Abu-Zaid; Ali El Miedany; Walaa Elwakil (Egyptian Rheumatology and Rehabilitation)
Abstract Background Polymyalgia rheumatica (PMR) and giant cell arteritis (GCA) frequently overlap, with each disease potentially presenting as a manifestation of the other. The strong relationship between PMR and GCA raises the question of whether it is a “co-occurrence of different diseases” or a “common spectrum of inflammatory diseases.” The objectives of the current study were to assess the applicability of using ultrasound (US) and clinical data as a monitoring tool to identify PMR patients with subclinical GCA and determine possible predictors of GCA among PMR patients. Results One hundred eight PMR patients and 62 GCA patients were included in this study. The study found that 20.4% of the PMR cohort had subclinical GCA, which later progressed to classical GCA, while 31.5% experienced a PMR relapse. The presence of intimal media thickening of the temporal/axillary artery at baseline was a very early predictor of GCA development; the OGUS score was significantly higher in the PMR group who developed GCA than the standard GCA cohort (p < 0.01). Conclusion The key finding of this study is the incorporation of the concept that vascular inflammation mainly precedes the classical clinical manifestations. Routine screening for subclinical GCA in PMR patients should be considered as part of standard care for PMR patients. Physicians should be attentive to the presence of mural inflammatory changes at the time of diagnosis and monitoring of the ultrasound composite scores in the follow-up course.